The Importance of Antioxidant Status in Gastric Intestinal Metaplasia: The Importance of Antioxidant Status in Intestinal Metaplasia - Danis, Nilay; Ertinmaz Ozkan, Aysegul; Karatas, Fatih; Cakici, Cagri; Yigitbasi, Turkan; Ozkan Sevencan, Nurhayat; Kayhan, Burcak (Journal of Medical Biochemistry, 2021)
Background and Aim: Oxidative stress status in different cancer types was investigated before, but not studied in gastric intestinal metaplasia to the best of our knowledge. Purpose of this study is to examine whether there is a difference between oxidative stress status in patients with intestinal metaplasia (IM) compared to individuals without IM, we compared the serum levels of disulfide (SS), total thiol (TT) and native thiol (NT).Patients and Methods: This was a prospective, non-randomized case-control study including 67 patients with histopathologically confirmed IM and 60 individuals demographically matched in terms of age, gender, BMI, smoking status, and chronic diseases as control group.Results: The mean NT, TT and NT to TT(NT/TT) ratios were statistically significantly higher in IM group compared to controls [(351.71±81.9µmol/L vs. 271.82±54.13µmol/L, p=0.000),(391.5±92.69µmol/L vs. 308.59±55.53 µmol/L, 0.000) and (0.89±0.6 vs. 0.87±0.29,  p=0.022), respectively].The mean SS to TT(SS/TT) ratio was significantly lower in IM group than control group (0.050±0.31 vs. 0.060±0.014, P=0.022). Median SS and mean SS/NT ratio was similar in both groups[16.3 (3.3 – 78) vs. 18.3 (10 – 32.7), p=0.271 and 0.055 ± 0.041 vs. 0.070 ± 0.019, p=0.068, respectively). In ROC analysis, cut off value of SS/NT for IM was found 0.062, in regression analysis, SS/NT